Radiation Preservation of Seafoods: A Case Study on Indian Mackerel - V., Venugopal; P.M., Nair (Fishery Technology, 2025)
Several aspects on the use of low dose gamma radiation for shelf life extension of Indian mackerel in ice have been examined to understand its amenability for the radiation process. These included, apart from determining the optimum dose (1.5 kGy) for maximum shelf life, storage studies in terms of sensory and chemical indices of freshness of the treated fish, influence of radiation on fish lipids, physico-chemical and functional properties of the fish proteins, textural attributes of the muscle and microbiological as well as wholesomeness aspects of the irradiated fish. Stability of the fish irradiated under non- packaged condition has also been studied with a view to adopt the method for large scale processing. This article consolidates these data and points out that Indian mackerel in ice could be irradiated at landing centres to achieve quality retention and hence enhanced marketability of the catch.